Hazelnut breeding in the National Dendrological Park “Sofiyivka” of the NAS of Ukraine - І. С. Косенко; А. І. Опалко; О. А. Балабак; О. А. Опалко; А. В. Балабак (Plant Varieties Studying and Protection)
Purpose. To evaluate hazelnut cultivars, species and hybrids from the genetic collection of Corylus spp. in the National Dendrological Park “Sofiyivka” of the NAS of Ukraine for the complex of economic characters. An attempt has been made to analyze the information on Corylus spp. identity, taxonomy and description, dissemination and ecological requirements of the species, possibilities to use the genetic potential for developing new cultivars.